Geotecnologias aplicadas ao estudo de desigualdades socioespaciais do espaço intraurbano goianiense (1991 – 2010) - Martins, Rubia Nara Silva (2014)
The issues involving the social spatial inequalities, urban segregation and social inclusion/exclusion in Goiânia, has been subject of studies and/or researches in the last few years. The central problem is that methodology for identification or mapping is not did integrated with a deep analyses with existing data. In this way, the proposal is use of geotechnologies like a support tool and/or improvement in the study of urban areas. So, this thesis has the central goal do available the social spatial inequalities in Goiânia, using the analysis for the social and economic data, with the methodology of treatment of georeferenced spatial data in GIS (Geographic Information System), with the bases the year of 2010. The used methodology involved a bibliographic research about the subjects involved at social spatial inequalities, segregation and geotechnologies; compilation of cartographic bases, construction and systematization of data; cartographic elaboration; in a exploring and quantification analysis for the social and economic profile in the Goiânia population. Based on the mapping and the related analysis, can be found that in Goiânia had a high horizontal growing in the last twenty years in the south and east areas in the city. The research showed the inequalities induced and self-segregation, and this process is marked in the territory with the social economic profile of population. And the population is directed, conditioning e segregated because of the agreements realized for the imobiliary agents with the government legitimation. The biggest part of the low income population is directing for the suburban areas in the city, because of the lower price of the soil, when they will get mobility and accessibility problems. While the richest class occupy a south and central portion in the city, with the entire basic infrastructure. The result is a contradictory situation in the city. By the way, is possible watch a small part the richest population living in the suburban areas with horizontal condos. In this way, the closed condos excluding this part of population to live in the ‘real’ city and follow their own standards inside the walls. The exclusionary distinguishing mark that you can find in Goiânia, in according with those business areas, is just the distance.